Oxidation behaviour of a next generation polycrystalline Mn containing Ni-based superalloy. (1st March 2016) - Pedrazzini, S.; Child, D.J.; West, G.; Doak, S.S.; Hardy, M.C.; Moody, M.P.; Bagot, P.A.J.
Abstract: A prototype next-generation superalloy containing 1 at.% Mn was oxidised in air at 800 °C for 100 h, and compared with a commercial Ni-based superalloy. The oxide scale consisted of a multi-phase layered structure measured by Atom Probe Tomography as uppermost NiCr2 Mn2 O4, followed by an inhomogeneous mix of Cr2 O3, spinel MnCr2 O4 and rutile (Ti, Cr)O2 . The Mn did not form a homogeneous, surface passivating oxide layer. Despite this, the alloy showed a 3 × reduction of oxide thickness compared to a commercial polycrystalline Ni-based superalloy. Graphical abstract: